FROM RECRUITMENT TO RETENTION: STRATEGIC MARKETING COMMUNICATION FOR HIGHER EDUCATION MANAGEMENT IN VIETNAM - Ly-Le, Tuong-Minh (Universitas Pelita Harapan, 2025)
This research investigates the dynamics of marketing communication (marcom) within Vietnamese universities, focusing on the balance between student recruitment and stakeholder engagement. The study aims to identify the key marcom activities, channels, and messaging strategies employed, assess the performance indicators and evaluation metrics, and explore how universities engage with stakeholders beyond prospective students. An in-depth interview approach was employed, involving ten representatives from higher education institutions in Vietnam. The findings reveal that Vietnamese universities predominantly focus their marcom efforts on student recruitment, with a combination of digital marketing and traditional methods like open days and school visits. Enrollment figures and digital metrics are the primary performance indicators used to assess effectiveness. However, the study highlights a lack of comprehensive communication strategies that encompass broader institutional goals and stakeholder engagement. The need for a balanced approach and alignment with institutional values is emphasized to enhance overall institutional competitiveness, support strategic planning, and contribute to education management practices. Abstrak dalam Bahasa Indonesia Penelitian ini mengkaji dinamika komunikasi pemasaran (marketing communication / marcom) di universitas-universitas Vietnam, dengan fokus pada keseimbangan antara perekrutan mahasiswa dan keterlibatan pemangku kepentingan. Studi ini bertujuan untuk mengidentifikasi aktivitas, saluran, dan strategi pesan utama yang digunakan dalam marcom; menilai indikator kinerja dan metrik evaluasi; serta mengeksplorasi bagaimana universitas menjalin hubungan dengan pemangku kepentingan selain calon mahasiswa. Pendekatan wawancara mendalam digunakan dalam penelitian ini, melibatkan sepuluh perwakilan dari institusi pendidikan tinggi di Vietnam. Temuan penelitian menunjukkan bahwa universitas di Vietnam secara dominan memfokuskan upaya marcom pada perekrutan mahasiswa, dengan memanfaatkan kombinasi pemasaran digital dan metode tradisional seperti open day dan kunjungan ke sekolah. Angka pendaftaran dan metrik digital menjadi indikator kinerja utama yang digunakan untuk menilai efektivitas. Namun, penelitian ini menyoroti kurangnya strategi komunikasi yang komprehensif yang mencakup tujuan kelembagaan yang lebih luas serta keterlibatan pemangku kepentingan. Kebutuhan akan pendekatan yang seimbang dan selaras dengan nilai-nilai institusi ditekankan guna meningkatkan daya saing kelembagaan secara keseluruhan, mendukung perencanaan strategis, dan berkontribusi pada praktik manajemen pendidikan.